Body Perception and Action Following Deafness - M. S. Houde; S. P. Landry; S. Pagé; M. Maheu; F. Champoux (Neural Plasticity)
The effect of deafness on sensory abilities has been the topic of extensive investigation over the past decades. These investigations have mostly focused on visual capacities. We are only now starting to investigate how the deaf experience their own bodies and body-related abilities. Indeed, a growing corpus of research suggests that auditory input could play an important role in body-related processing. Deafness could therefore disturb such processes. It has also been suggested that many unexplained daily difficulties experienced by the deaf could be related to deficits in this underexplored field. In the present review, we propose an overview of the current state of knowledge on the effects of deafness on body-related processing.